Pengaruh Lingkungan Kerja Dan Kepemimpinan Terhadap Kinerja Pegawai Bappeda Kabupaten Tangerang: The Influence of Work Environment and Leadership on the Performance of Employees at the Regional Development Planning Agency (Bappeda) of Tangerang Regency - Keysa Ananda Delly; Ratih Hastasari; Wawan Saputra (CV Warnak Johanna Nusantara, 2025)
Human resources are the main asset of an organization, including public sector institutions such as the Regional Development Planning Agency (Bappeda). Optimal employee performance is essential to achieving organizational goals and providing quality public services. This study aims to examine the influence of work environment and leadership on employee performance at Bappeda of Tangerang Regency. The study is motivated by issues related to inadequate workspace conditions and a top- down leadership style with limited communication. This research employs a descriptive quantitative method, with data collected through questionnaires distributed to 58 respondents. The data were analyzed using SPSS software through various statistical tests including validity, reliability, normality, t-test, F-test, and coefficient of determination. The results indicate that the work environment (X1) has a partial influence on employee performance with a t-value of 4.008 > t-table 2.004, and leadership (X2) also has a partial influence with a t-value of 2.798 > t-table 2.004. Simultaneously, both variables significantly affect employee performance with an F- value of 41.758 > F-table 3.16. The R square value of 50.5% indicates that employee performance is moderately influenced by work environment and leadership